1991
DOI: 10.1007/bf00329408
|View full text |Cite
|
Sign up to set email alerts
|

Secretion of the overproduced periplasmic PhoA protein into the medium and accumulation of its precursor in phoA-transformed Escherichia coli strains: involvement of outer membrane vesicles

Abstract: Various Escherichia coli strains were transformed by multicopy plasmids pHI-1, pHI-7 and pPHOI carrying the entire regulatory and structural phoA sequences. All transformants with the intact pho regulatory system displayed PhoA oversynthesis and secretion into the medium. They also accumulated the alkaline phosphatase precursor localized in the outer membrane fraction. The dynamics of enzyme synthesis and secretion as well as cell cytomorphology during secretion were studied in strain E. coli K12 802 carrying … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

1998
1998
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 31 publications
1
10
0
Order By: Relevance
“…The periplasmic nonspecific acid phosphatases are known to concentrate at cell poles in Gram-negative bacteria (41)(42)(43). In accordance with this, the E. coli(pPN1) cells under GC1 displayed a periplasmic location of the precipitate at the poles (within the cells).…”
Section: Discussionmentioning
confidence: 58%
“…The periplasmic nonspecific acid phosphatases are known to concentrate at cell poles in Gram-negative bacteria (41)(42)(43). In accordance with this, the E. coli(pPN1) cells under GC1 displayed a periplasmic location of the precipitate at the poles (within the cells).…”
Section: Discussionmentioning
confidence: 58%
“…The phosphate ligand originates from the product of the phosphohydrolytic reaction; the mediating phosphatase, homologous to the phoN product of various other enterobacteria (Macaskie et al 1994b), was identified as atypical in preliminary (Hambling et al 1987) and comparative (Montgomery et al 1995) studies. The possible biotechnological application of this class of phosphatase prompted this fundamental study of the properties of the Citrobacter enzyme and its comparison to that described in Salmonella typhimurium (Kier et al 1977a(Kier et al ,b, 1979Weppelman et al 1977) and alkaline phosphatase processing-related phenomena described in Escherichia coli (Nesmeyanova et al 1991(Nesmeyanova et al , 1994.…”
Section: Introductionmentioning
confidence: 96%
“…Recognition of signal sequences by a targeting factor is a very well coordinated and balanced process. When this balance is disrupted by overproduction of secretory proteins their precursors are accumulated in the cytoplasm in bacteria [21, 22]. In mammals, inability of a mutated protein to interact with SRP triggers a specific quality control mechanism, RAPP [23].…”
Section: Introductionmentioning
confidence: 99%